Effects of Poisoning on Serum Enzyme Activities, Coagulation, and Fibrinolysis. Issue 5770 (7th August 1971) - Wright, N.; Clarkson, A. R.; Brown, S. S.; Fuster, V.
Abstract : Prolonged coma due to acute overdosage with hypnotic drugs is shown to be associated with a pronounced increase in the activity of serum creatine kinase and in the concentration of fibrin degradation products and with less pronounced abnormalities of other serum enzymes and of other indices of coagulation and fibrinolysis. Evidence is presented that skeletal muscle damage occurs and that this is related to the coagulation abnormality. These findings probably explain some of the non-specific features such as fever which commonly occur in recovery from severe poisoning.